DESCRIPTION ABOUT POLICE’S AGGRESSIVE BEHAVIOR AGAINST DEMONSTRATION - Agus Sapari; Ni Made Taganing Kurniati (Jurnal Psikologi, 2007)
Reformation era has been running for long time in Indonesia, including the free of make an opinion in the public space. But the fact shows sometimes the demonstration has been showed off in a rude way. When this happened, the police shows repressive act againts the demonstration. This fact is ironic because the repressive acts done by the police. The aim of this study is to know the description about police’s aggresion against the demonstration. The participants are police men who ever done the aggresive behavior against the demonstration. The data is collected by some test such as EPPS and DAP. The result shows that the aggresion showed by the police is just a response to the aggression done by the demonstration.Key words: aggresive behavior, policemen, demonstration